PRELIMINARY RESEARCH INTO TRANSLATION OF CHINESE VAGUE TERMS AND GENERAL CLAUSES - GRZYBEK, Joanna (Comparative Legilinguistics, 2013)
Vague terms and general clauses are a challenge for legal translators whose legal and extra-legal knowledge affect the interpretetion of the source text and its translation. Research into terminology and comparative law reveals that the meanings of many vague terms and general clauses occurring in parallel texts in various legal languages differ due to divergent legal systems and cultures. The author analyses the stances of legal translators and lawyers on specific features of vague terms and general clauses as well as discrepancies between their meanings. The author aims at revealing a need to carry out research into Chinese vague terms and general clauses.